Composite resin particles, composite resin foam particles, and foamed molded product
The composite resin particles containing polyacrylonitrile, ethylene-vinyl acetate copolymer and polystyrene were prepared by seed polymerization, which solved the problems of high energy consumption and insufficient fire resistance of foaming high thermal resistance and low-density foaming under low steam pressure, and achieved efficient and low-cost foam production.
Patent Information
- Application Number
- JP2023509132
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2022-03-18
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2042-03-18
AI Technical Summary
In the prior art, when preparing high thermal resistance and low density polystyrene foam plastics, there are problems such as high steam pressure demand, which leads to high energy consumption and high equipment costs. At the same time, the fire resistance and impact resistance of the foam plastics are insufficient.
Foam plastic is prepared by seed polymerization using composite resin particles including polyacrylonitrile, ethylene-vinyl acetate copolymer and polystyrene. By controlling the resin composition and proportion, stable foaming is achieved under low steam pressure, and flame retardant is added to improve fire resistance and impact resistance.
It realizes the preparation of foam plastics with no discoloration, good fire resistance and strong impact resistance under low steam pressure, reducing production energy consumption and equipment costs, and improving the mechanical strength and stability of foam plastics.
Smart Images

Figure 0007627745000001 
Figure 0007627745000002 
Figure 0007627745000003
Abstract
Description
[Technical field]
[0001] The present invention relates to composite resin particles, expanded composite resin beads, expanded molded articles, and the like. [Background technology]
[0002] It is known that foamed molded articles made of polystyrene resins are excellent in rigidity, heat insulation, light weight, water resistance, and foam moldability, but have low chemical resistance and impact resistance. To compensate for this, composite resin foamed molded articles obtained from composite resin particles of polystyrene resin and polyolefin resin are used. Composite resin particles are generally produced by using a base resin of a polyolefin resin such as a polyethylene resin as a seed particle (also called a core particle), adding a styrene monomer to the seed particle, and then polymerizing it. This polymerization is also called seed polymerization. The composite resin particles are generally foamed (also called pre-foamed) after mixing with a foaming gas to become foamed particles (foamed particles), and the foamed particles are filled into a mold and heated to produce a foamed molded article.
[0003] The properties of the composite resin foam molded body can be changed by changing the type of polyolefin resin constituting the composite resin particles. For example, the use of polypropylene resin improves heat resistance, and the use of linear low-density polyethylene improves impact resistance. Composite resin foam molded bodies with high heat resistance are in demand, mainly for automobile parts, and composite resin foam molded bodies with excellent heat resistance obtained from composite resin particles made of polypropylene resin and polystyrene resin have been used (Patent Document 1). However, if the pressure of the steam used for foam molding is not high, foaming becomes insufficient and it is difficult to obtain a molded body with the desired shape, density, and other properties. If the pressure of the steam required for foam molding is high, more energy is required for molding, and a molding machine that can handle that pressure must be used, which increases the cost of molding.
[0004] For this reason, particles of composite resins obtained by compounding a base resin made of high-density polyethylene and an ethylene copolymer (e.g., an ethylene-vinyl acetate copolymer) with a polystyrene resin by seed polymerization have been used as an alternative. The use of these particles makes it possible to carry out foam molding without increasing the steam pressure very much (Patent Documents 2 and 3). Furthermore, because foam molded articles used as automotive components are often required to be flame retardant, flame retardants have been incorporated into these foam molded articles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4718645 [Patent Document 2] JP 2015-189912 A [Patent Document 3] Patent No. 6251409 Summary of the Invention [Problem to be solved by the invention]
[0006] The present inventors have noticed that when a flame retardant is blended into a composite resin obtained by compounding a base resin consisting of high-density polyethylene and an ethylene-vinyl acetate copolymer with a polystyrene-based resin through seed polymerization, the foamed molded article becomes colored reddish in an accelerated storage stability test.
[0007] An object of the present invention is to provide a foamed molded product that has excellent heat resistance (low rate of dimensional change upon heating), excellent flame retardancy, and no coloring in an accelerated test of storage stability, and composite resin particles and the like for producing the same. Another object of the present invention is to provide composite resin particles that generate a reduced amount of powder during production of the composite resin foamed beads. An object of the present invention is to provide composite resin foamed beads that have excellent moldability and can be foamed at steady air pressure due to their high fusibility at low vapor pressure. An object of the present invention is to provide a foamed molded product that has excellent bending strength. An object of the present invention is to provide a foamed molded product that has excellent impact resistance. [Means for solving the problem]
[0008] In view of the above problems, the present inventors have discovered that by foaming molding composite resin particles containing a polypropylene-based resin, an ethylene-vinyl acetate copolymer, and a polystyrene-based resin, and foamed resin particles obtained therefrom, it is possible to obtain a foamed molded article that does not discolor in an accelerated storage stability test, and that this foamed molded article has high flame retardancy and excellent heat resistance (low rate of dimensional change upon heating) brought about by the polypropylene-based resin, and have completed the present invention.
[0009] The present invention typically includes the following aspects. Section 1. Composite resin particles containing a polypropylene-based resin, an ethylene-vinyl acetate copolymer, and a polystyrene-based resin. Section 2. Item 2. The composite resin particles according to item 1, wherein the content of the polypropylene resin is 2 to 35 mass%, the content of the ethylene-vinyl acetate copolymer is 3 to 50 mass%, and the content of the polystyrene resin is 40 to 95 mass%, based on the total mass of the composite resin particles. Section 3. 3. The composite resin particles according to item 1 or 2, wherein the content of the ethylene-vinyl acetate copolymer in the composite resin particles is 60 to 1000 parts by mass per 100 parts by mass of the polypropylene resin. Section 4. the content of the ethylene-vinyl acetate copolymer in the composite resin particles is 10 to 60 parts by mass relative to 100 parts by mass of the polypropylene-based resin; Item 3. The composite resin particle according to item 1 or 2, wherein the polystyrene-based resin contains a resin component derived from a (meth)acrylic acid ester and a resin component derived from a styrene-based monomer, and the resin component derived from the (meth)acrylic acid ester is contained in an amount of 0.05 to 5.00 mass% of the mass of the resin component derived from the styrene-based monomer. Section 5. Item 5. The composite resin particles according to any one of items 1 to 4, wherein the total mass content of the polypropylene-based resin and the ethylene-vinyl acetate copolymer in the composite resin particles / the mass content of the polystyrene-based resin in the composite resin particles is 5 / 95 to 60 / 40. Section 6. Item 6. The composite resin particles according to any one of items 1 to 5, wherein the ethylene-vinyl acetate copolymer has a melting point of 100 to 120°C. Section 7. Item 7. The composite resin particles according to any one of Items 1 to 6, wherein the ethylene-vinyl acetate copolymer has a ratio (Mw / Mn) of its mass average molecular weight (Mw) to its number average molecular weight (Mn) of 1.0 to 7.0. Section 8. Item 8. The composite resin particles according to any one of Items 1 to 7, wherein the ethylene-vinyl acetate copolymer has a melt flow rate of 0.5 g / 10 min to 10 g / 10 min. Section 9. Item 9. The composite resin particles according to any one of items 1 to 8, wherein the polypropylene resin has a melting point of 130 to 150°C. Section 10. Item 10. The composite resin particles according to any one of items 1 to 9, wherein the polypropylene resin is a random polypropylene. Section 11. 11. The composite resin particles according to any one of items 1 to 10, further comprising a flame retardant in an amount of 0.5 to 10% by mass of the composite resin particles excluding the flame retardant. Section 12. Item 12. The composite resin particle according to item 11, wherein the flame retardant is a halogen-based flame retardant. Section 13. Item 13. The composite resin particles according to any one of items 1 to 12, further comprising an inorganic component, the content of which is 0.01 to 5% by mass of the composite resin particles. Section 14. Item 14. The composite resin particle according to item 13, wherein the inorganic component is talc or silica. Section 15. Item 15. The composite resin particles according to any one of items 1 to 14, which are seed polymerization particles obtained by impregnating and polymerizing seed particles containing the polypropylene resin and the ethylene-vinyl acetate copolymer with a styrene monomer. Section 16. Item 16. Expanded beads made of the composite resin beads according to any one of items 1 to 15. Section 17. Bulk density: 10kg / m 3 ~200kg / m 3 Item 16. The expanded particles according to item 15, Section 18. Item 18. A foamed molded article comprising the foamed beads according to item 16 or 17. Section 19. Density: 20kg / m 3 ~50kg / m 3 Item 19. The foam molded article according to item 18, wherein Section 20. Item 18. An automotive component comprising the foamed molded article according to item 18 or 19. Effect of the Invention
[0010] The composite resin particles and composite expanded beads of the present invention can provide an expanded molded article that does not become discolored in an accelerated storage stability test. The composite resin particles and composite expanded particles of the present invention can provide an expanded molded article having high flame retardancy and excellent heat resistance (low rate of dimensional change due to heating) provided by the polypropylene-based resin. According to the composite resin particles of the present invention, the amount of powder generated during the production of the expanded composite resin beads (also referred to simply as "powder amount" in this specification) is reduced, so that the life of a mold can be extended. The composite resin particles and composite resin particles of the present invention enable expansion molding with a high thermal fusion rate even when using a medium with a low vapor pressure (e.g., water vapor), so that the energy required for expansion molding can be reduced. This allows the equipment required for expansion molding to be simplified, and the cost required for expansion molding to be reduced. Therefore, the composite resin particles and expanded composite resin particles of the present invention are excellent in productivity for expansion molding. The composite resin particles and composite expanded beads of the present invention can provide expanded molded articles having excellent bending strength. The composite resin particles and composite expanded beads of the present invention can provide expanded molded articles having excellent impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As used herein, the phrase "comprising" is intended to encompass the phrases "consisting essentially of" and "consisting of."
[0012] The composite resin particles are typically obtained by impregnating base resin particles (seed particles) with a styrene-based monomer and polymerizing the styrene-based monomer. The base resin contains at least a polypropylene-based resin and an ethylene-vinyl acetate copolymer. The total content of the polypropylene-based resin and the ethylene-vinyl acetate copolymer in the seed particles may be, for example, 80 to 100 mass%, 85 to 100 mass%, 90 to 100 mass%, 95 to 100 mass%, etc., based on the total mass of the seed particles.
[0013] (Polypropylene resin) The polypropylene resin is not particularly limited, and known resins can be used. Examples of the polypropylene resin include homopolymers, random copolymers, block copolymers, etc., and random copolymers are preferred because of their high moldability (i.e., because they have high fusibility at low vapor pressure, they can be foamed and the foaming ratio during foaming tends to be high). As the polypropylene-based resin, recycled products, for example polypropylene-based resins used as packaging materials, etc., may be collected and recycled, and recycled resins may be used.
[0014] The copolymer may contain an olefin other than propylene (e.g., ethylene, butene, etc.). Examples of the random copolymer include an ethylene-propylene random copolymer, a propylene-butene random copolymer, and an ethylene-propylene-butene random copolymer. Examples of the block copolymer include an ethylene-propylene block copolymer, a propylene-butene block copolymer, and an ethylene-propylene-butene block copolymer. The proportion of components derived from olefins other than propylene in the copolymer can be, for example, 0.01 to 10 mass%, 0.01 to 8 mass%, 0.1 to 7 mass%, 0.1 to 6 mass%, etc., preferably 1 to 7 mass%, and more preferably 2 to 6 mass%. As the polypropylene-based resin, commercially available resins can be used, for example, those available from Prime Polymer Co., Ltd., SunAllomer Co., Ltd., Sumitomo Chemical Co., Ltd., etc.
[0015] The melting point of the polypropylene resin is not particularly limited, but can be, for example, 130 to 165°C, preferably 130 to 150°C, more preferably 130 to 145°C, and even more preferably 130 to 134°C. If the melting point is within the above range, it is advantageous in that moldability (high fusion rate) at low vapor pressure is improved or the expansion ratio during foaming is easily increased. The melting point can be determined by the method described in the examples.
[0016] The melt mass flow rate (also referred to as MFR in this specification) of the polypropylene resin is not particularly limited, but is preferably 0.1 g / 10 min to 20.0 g / 10 min, more preferably 1 g / 10 min to 10 g / 10 min, and particularly preferably 4 g / 10 min to 8 g / 10 min. If the MFR is within the above range, it is advantageous in terms of foam moldability. The MFR can be determined by the method described in the examples.
[0017] Polypropylene resin: 880kg / m 3 ~950kg / m 3 The density may be within this range, which is advantageous in terms of impact resistance and moldability. The density may be 890 kg / m 3 ~930kg / m 3 is preferred, and 890 kg / m 3 ~920kg / m 3 More preferably, 890 kg / m 3 ~910kg / m 3 It is particularly preferable that the density is within the above range. It is advantageous in terms of foam moldability. The density can be specified by the following method. (Density of polypropylene resin) The density of the polypropylene resin is measured by the density gradient tube method in accordance with JIS K6922-1:1998.
[0018] The content ratio of the polypropylene-based resin in the seed particles relative to the total mass of the seed particles can be, for example, 10 to 77 mass%, 10 to 70 mass%, 10 to 60 mass%, 15 to 50 mass%, 18 to 70 mass%, etc., preferably 18 to 60 mass%, more preferably 18 to 50 mass%, and even more preferably 18 to 40 mass%. When the polystyrene-based resin contains a resin component derived from a (meth)acrylic acid ester, the content ratio of the polypropylene-based resin in the seed particles can be, for example, 10 to 95 mass%, 10 to 90 mass%, 20 to 80 mass%, 30 to 80 mass%, etc., relative to the total mass of the seed particles, preferably 18 to 90 mass%, more preferably 18 to 80 mass%, and even more preferably 30 to 80 mass%. The content of the polypropylene resin in the composite resin particles can be, for example, 2 to 35 mass %, preferably 4 to 30 mass %, and more preferably 5 to 20 mass %, based on the total mass of the composite resin particles. When the polystyrene-based resin contains a resin component derived from a (meth)acrylic acid ester, the content of the polypropylene-based resin in the composite resin particles can be, for example, 2 to 35 mass% relative to the total mass of the composite resin particles, preferably 4 to 31 mass%, and more preferably 9 to 31 mass%. If the content of the polypropylene resin in the seed particles or composite resin particles is within the above range, it is advantageous in terms of a small rate of dimensional change upon heating or flame retardancy.
[0019] (Ethylene-vinyl acetate copolymer) Ethylene-vinyl acetate copolymer is a copolymer of ethylene and vinyl acetate. Ethylene-vinyl acetate copolymer is superior to copolymers of ethylene and other ester monomers (e.g., alkyl acrylates, alkyl methacrylates, vinyl aliphatic saturated monocarboxylates (excluding vinyl acetate)) in that it generates less powder during the production of composite resin foam particles and has a smaller rate of dimensional change upon heating. As the ethylene-vinyl acetate copolymer, recycled products, for example, recycled resins obtained by recovering ethylene-vinyl acetate copolymers used as packaging materials and the like, can also be used.
[0020] The proportion of the vinyl acetate-derived component in the ethylene-vinyl acetate copolymer is preferably 1 to 20 mass %, more preferably 1 to 14 mass %, and even more preferably 1 to 10 mass %.
[0021] The melting point of the ethylene-vinyl acetate copolymer is not particularly limited, but can be, for example, 85 to 120° C., preferably 100 to 120° C., more preferably 100 to 115° C., and even more preferably 100 to 110° C. If the melting point is within the above range, it is advantageous in that the thermal dimensional change rate of the foamed molded product is small or that the compatibility with polypropylene-based resin is good, resulting in excellent fusion properties during foam molding. The melting point can be determined by the method described in the examples.
[0022] The ratio (Mw / Mn) of the mass average molecular weight (Mw) of the ethylene-vinyl acetate copolymer to the number average molecular weight (Mn) of the ethylene-vinyl acetate copolymer is not particularly limited, but may be, for example, 1.0 to 7.5, and is preferably 1.0 to 7.0. Mw / Mn within the above range is advantageous in that the strength of the foamed molded article is high or the impact resistance is improved. Mw / Mn is more preferably 3.0 to 6.0, and even more preferably 3.5 to 5.5. The number average molecular weight and mass average molecular weight can be determined by the method described in the examples.
[0023] The MFR of the ethylene-vinyl acetate copolymer is not particularly limited, but can be, for example, 0.3g / 10min to 5.0g / 10min, preferably 0.5g / 10min to 5.0g / 10min. If the MFR is within the above range, it is advantageous in that the strength of the foamed molded product is high, the impact resistance is improved, or the moldability (high fusion rate) at low vapor pressure is improved. The MFR is more preferably 0.5g / 10min to 4.0g / 10min, even more preferably 0.5g / 10min to 3.0g / 10min, and particularly preferably 0.7g / 10min to 3.0g / 10min. The MFR can be determined by the method described in the examples.
[0024] The content ratio of the ethylene-vinyl acetate copolymer in the seed particles relative to the total mass of the seed particles can be, for example, 27 to 90 mass%, 30 to 90 mass%, 40 to 90 mass%, 50 to 85 mass%, 30 to 82 mass%, etc., preferably 40 to 82 mass%, more preferably 50 to 82 mass%, and even more preferably 60 to 82 mass%. When the polystyrene-based resin contained in the composite resin particles contains a resin component derived from a (meth)acrylic acid ester, the content ratio of the ethylene-vinyl acetate copolymer in the seed particles can be, for example, 5 to 90 mass%, 10 to 90 mass%, 20 to 80 mass%, 20 to 70 mass%, etc., relative to the total mass of the seed particles, preferably 10 to 82 mass%, more preferably 20 to 82 mass%, and even more preferably 20 to 70 mass%. The content of the ethylene-vinyl acetate copolymer in the composite resin particles can be, for example, 3 to 50 mass %, preferably 5 to 40 mass %, and more preferably 10 to 30 mass %, based on the total mass of the composite resin particles. When the polystyrene resin contained in the composite resin particles contains a resin component derived from a (meth)acrylic acid ester, the content of the ethylene-vinyl acetate copolymer in the composite resin particles can be, for example, 3 to 50 mass %, preferably 3 to 40 mass %, and more preferably 3 to 30 mass %, relative to the total mass of the composite resin particles. If the content of the ethylene-vinyl acetate copolymer in the seed particles or the composite resin particles is within the above range, it is advantageous in terms of molding processability or flame retardancy.
[0025] The ethylene-vinyl acetate copolymer content in the seed particles or composite resin particles can be, for example, 60 to 1,000 parts by mass, 80 to 1,000 parts by mass, etc., relative to 100 parts by mass of the polypropylene resin content, preferably 100 to 1,000 parts by mass, more preferably 120 to 1,000 parts by mass, and even more preferably 130 to 1,000 parts by mass. When the polystyrene-based resin contains a resin component derived from a (meth)acrylic acid ester, the ethylene-vinyl acetate copolymer content in the seed particles or composite resin particles can be, for example, 10 to 1,000 parts by mass, 10 to 500 parts by mass, etc., preferably 20 to 500 parts by mass, and more preferably 20 to 300 parts by mass, relative to 100 parts by mass of the polypropylene-based resin content. When the content of the ethylene-vinyl acetate copolymer is within the above range, it is advantageous in that the moldability at low vapor pressure is improved (the fusion rate is increased).
[0026] (Inorganic component) The seed particles may contain an inorganic component in addition to the polypropylene resin and the ethylene-vinyl acetate copolymer. When the seed particles or the composite resin particles contain an inorganic component, the bubbles are easily made fine. Examples of the inorganic component include inorganic bubble regulators such as talc, silica, calcium silicate, calcium carbonate, sodium borate, and zinc borate, and talc and silica are preferred because they are easy to homogenize the bubble size. The inorganic component can be, for example, 0.01 to 5% by mass, and preferably 0.1 to 1% by mass, based on the total mass of the polypropylene resin and the ethylene-vinyl acetate copolymer. The inorganic component may be added when the polypropylene resin and the ethylene-vinyl acetate copolymer are mixed, or may be added to a mixed resin in which the polypropylene resin and the ethylene-vinyl acetate copolymer are mixed.
[0027] (carbon component) The seed particles may contain a carbon component in addition to the polypropylene resin and the ethylene-vinyl acetate copolymer. Examples of the carbon component include furnace black, ketjen black, channel black, thermal black, acetylene black, graphite, and carbon fiber. The carbon component added to the seed particles is preferably particulate, and the average particle diameter may be 5 nm to 100 nm, and is preferably 15 nm to 35 nm. The average particle diameter of the carbon component is the average value of particle diameters observed by an electron microscope. However, when the carbon component is carbon black, the average particle diameter of the carbon black is the average value of particle diameters measured and calculated by measuring small spherical (having an outline due to microcrystals and being inseparable) components constituting the carbon black aggregates in an electron microscope photograph. The carbon component is preferably contained in an amount of 1 to 8 mass % based on the total mass of the polypropylene resin and the ethylene-vinyl acetate copolymer. When the amount of carbon in the composite resin particles is within the above range, the foamed molded article has a sufficient black color and also has sufficient mechanical strength.
[0028] (Other ingredients) The seed particles may contain other components in addition to the polypropylene resin and the ethylene-vinyl acetate copolymer. Examples of the other components include colorants, nucleating agents, stabilizers, fillers (reinforcing agents), higher fatty acid metal salts, antistatic agents, lubricants, natural or synthetic oils, waxes, UV absorbers, weather stabilizers, antifogging agents, antiblocking agents, slip agents, coating agents, and neutron shielding agents. When the seed particles contain other components, the content of the other components may be 0.001 to 10% by mass, preferably 0.001 to 5% by mass or less, and more preferably 0.001 to 3% by mass, based on the total mass of the seed particles.
[0029] (Seed particle manufacturing method) The seed particles can be obtained by a known method used for producing seed particles for forming foamed molded bodies. For example, a base resin (polyethylene resin, ethylene copolymer, etc.) is melt-kneaded in an extruder and extruded to obtain strands, and the obtained strands are cut in air, in water, or while being heated to form granules. The resin components may be mixed in a mixer before being fed into the extruder.
[0030] The seed particles may have any known shape, but are preferably cylindrical, elliptical (egg-shaped) or spherical, and more preferably elliptical or spherical in shape, from the viewpoint of good fillability of the expanded beads obtained from the seed particles into a mold. The seed particles preferably have an average particle size of 0.5 to 1.4 mm.
[0031] (composite resin particles) The composite resin particles contain, as resin components, a polypropylene resin and an ethylene copolymer derived from a base resin, and a polystyrene resin derived from a styrene monomer. The total content of the polypropylene resin, the ethylene-vinyl acetate copolymer, and the polystyrene resin in the composite resin particles may be, for example, 80 to 100 mass%, 85 to 100 mass%, 90 to 100 mass%, 95 to 100 mass%, etc., based on the total mass of the composite resin particles. The composite resin particles can be produced, for example, by a seed polymerization method (impregnating and polymerizing seed particles with a styrene monomer).
[0032] In the seed polymerization, the amount of the styrene-based monomer used is preferably such that the total mass of the polypropylene-based resin and the ethylene-vinyl acetate copolymer contained in the seed particles / the amount of the styrene monomer used is 5 / 95 to 60 / 40. Here, the content of the polystyrene-based resin in the composite resin particles is an amount corresponding to the amount of the styrene-based monomer used. Therefore, the total mass of the polypropylene-based resin and the ethylene-vinyl acetate copolymer contained in the composite resin particles / the mass of the polystyrene-based resin contained in the composite resin particles is preferably 5 / 95 to 60 / 40. If the amount of the styrene-based monomer used or the polystyrene-based resin content is within the above range, it is advantageous in that the moldability at low vapor pressure (high fusion rate) is improved, the powder amount is reduced, the strength of the foamed molded product is improved, or the impact resistance of the foamed molded product is improved. The range is more preferably 5 / 95 to 55 / 45, even more preferably 10 / 90 to 50 / 50, even more preferably 20 / 80 to 45 / 55, and particularly preferably 20 / 80 to 30 / 70.
[0033] Examples of polystyrene resins include polymers derived from styrene monomers such as styrene, α-methylstyrene, p-methylstyrene, and t-butylstyrene. Furthermore, the styrene polymer may be a polymer formed from a styrene monomer and another monomer copolymerizable with the styrene monomer. Examples of the other monomer include a polyfunctional monomer such as divinylbenzene, and a (meth)acrylic acid ester that does not contain a benzene ring in the structure such as butyl (meth)acrylate. The resin components derived from these other monomers may be contained in the styrene polymer in an amount not exceeding 5% by mass.
[0034] A polystyrene-based resin in which a (meth)acrylic acid ester is copolymerized with a styrene-based monomer is composed of a component derived from a (meth)acrylic acid ester and a component derived from a styrene-based monomer. The component derived from a (meth)acrylic acid ester is also called a resin component derived from a (meth)acrylic acid ester. The (meth)acrylic acid ester may be either an acrylic acid ester or a methacrylic acid ester, but is preferably an acrylic acid ester. Examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, among which methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, and 2-ethylhexyl acrylate are preferred, and butyl acrylate is more preferred.
[0035] The content of the resin component derived from the (meth)acrylic acid ester may be 0.05 to 5.00 mass% relative to the mass of the resin component derived from the styrene monomer, and is preferably 0.05 to 3.00 mass%. For example, in Example 8, 300 g of styrene monomer, 20 g of butyl acrylate, and 1080 g of styrene monomer are used as the polystyrene resin, so the content of the resin component derived from the butyl acrylate is 1.45% (20 / (300+1080)×100). When the content ratio of the resin component derived from the (meth)acrylic acid ester is within the above range, expansion molding of expanded beads having a high content ratio of polypropylene-based resin can be easily performed even if the vapor pressure of the heating medium during expansion molding is not high.
[0036] (Flame retardant) The composite resin particles may contain a flame retardant. In addition, since the composite resin particles have a relatively high flame retardancy even without a flame retardant, they do not need to contain a flame retardant (e.g., a halogen-based flame retardant).
[0037] Examples of the flame retardant include known halogen-based flame retardants, phosphorus-based flame retardants, inorganic flame retardants, etc. The flame retardant may be used alone or in combination of two or more. When the composite resin particles contain a flame retardant, a halogen-based flame retardant such as a bromine-based flame retardant, a chlorine-based flame retardant, or a chlorine-bromine-containing flame retardant is preferred as the flame retardant from the viewpoint that a small amount of the flame retardant can impart high flame retardancy to the foamed molded article.
[0038] Examples of halogen-based flame retardants include tetrabromobisphenol A, derivatives thereof (e.g., tetrabromobisphenol A bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol A bis(2,3-dibromopropyl ether), tetrabromobisphenol A bis(allyl ether)), triallyl isocyanurate hexabromide, tris(2,3-dibromopropyl)isocyanurate, tetrabromocyclooctane, and hexabromocyclododecane.
[0039] Generally, when a halogen-based flame retardant is contained, the flame retardancy of the foamed molded article is improved, but the heat resistance of the foamed molded article tends to decrease. However, the foamed molded article of the present invention has a low rate of dimensional change upon heating, and therefore the decrease in heat resistance is small.
[0040] The content of the flame retardant can be, for example, 1.5 to 6.0 mass %, preferably 1.5 to 4.0 mass %, and more preferably 2.0 to 3.5 mass %, based on the mass of the composite resin particles excluding the flame retardant. If the content of the flame retardant is within the above range, it is advantageous in that the flame retardancy and heat resistance of the foamed molded article can be simultaneously achieved at a high level.
[0041] When the composite resin particles contain a flame retardant, it is preferable that the composite resin particles contain a flame retardant assistant. By containing the flame retardant assistant, the flame retardancy brought about by the flame retardant can be further improved. Examples of the flame retardant assistant include organic peroxides such as dicumyl peroxide (DCP), cumene hydroperoxide, and diacyl peroxide, 2,3-dimethyl-2,3-diphenylbutane (also known as biscumyl), and 3,4-dimethyl-3,4-diphenylhexane. The flame retardant synergist is preferably contained in an amount of, for example, 50 parts by mass or less, preferably 10 to 40 parts by mass, and more preferably 15 to 25 parts by mass, per 100 parts by mass of the flame retardant. When the content of the flame retardant synergist is within the above range, the deterioration of the impact resistance and heat resistance of the foamed molded article is suppressed.
[0042] The shape of the composite resin particles may be any known shape, but cylindrical, approximately spherical, and spherical shapes are preferred, and approximately spherical or spherical shapes are more preferred in that the composite resin foamed beads formed from the composite resin particles have good fillability into a mold. The average particle size of the composite resin particles is preferably 0.6 mm to 1.8 mm in terms of the excellent fillability of the expanded composite resin particles into a mold.
[0043] (Method of manufacturing composite resin particles) The method for producing the composite resin particles is not particularly limited as long as the composite resin particles described above can be obtained. As an example, the composite resin particles can be obtained by the following production method. That is, the composite resin particles can be obtained by polymerizing the styrene monomer impregnated into the seed particles. This method is a so-called seed polymerization method.
[0044] An example of a method for producing composite resin particles using the seed polymerization method will be described below. First, seed particles, a styrene-based monomer, and, if necessary, a polymerization initiator are dispersed in an aqueous suspension. When a polymerization initiator is used, the styrene-based monomer and the polymerization initiator may be mixed in advance.
[0045] As the polymerization initiator, those generally used as initiators for suspension polymerization of styrene-based monomers can be suitably used. For example, organic peroxides such as benzoyl peroxide, di-t-butyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butyl peroxyhexane, t-butyl peroxy-3,5,5-trimethylhexanoate, and t-butyl-peroxy-2-ethylhexyl carbonate, and azo compounds such as azobisisobutyronitrile and azobisdimethylvaleronitrile. These polymerization initiators can be used alone or in combination. Dicumyl peroxide can also act as a flame retardant assistant. Examples of the aqueous medium constituting the aqueous suspension include water and a mixed medium of water and a water-soluble solvent (for example, a lower alcohol).
[0046] The amount of the polymerization initiator used is preferably from 0.01 to 0.9 parts by mass, and more preferably from 0.1 to 0.5 parts by mass, based on 100 parts by mass of the styrene-based monomer.
[0047] A dispersant may be added to the aqueous suspension as necessary. The dispersant is not particularly limited, and any known dispersant may be used. Specific examples include poorly soluble inorganic substances such as calcium phosphate, magnesium pyrophosphate, sodium pyrophosphate, and magnesium oxide. Furthermore, a surfactant such as sodium dodecylbenzenesulfonate may be used.
[0048] Next, the obtained dispersion is heated to a temperature at which the styrene-based monomer is not substantially polymerized, so that the styrene-based monomer is impregnated into the seed particles. The time for impregnating the seed particles with the styrene-based monomer is not particularly limited and can be, for example, 1 minute to 24 hours, but is preferably 20 minutes to 4 hours, and more preferably 30 minutes to 2 hours.
[0049] Next, the styrene monomer is polymerized. The polymerization is not particularly limited, but is preferably carried out at 115 to 150°C, preferably 120 to 140°C, for 1.5 to 5 hours. The polymerization is usually carried out in a pressurizable sealed container. It is preferable to carry out the impregnation of the styrene monomer and the polymerization several times (for example, two, three, four times, etc.). By carrying out the process several times, the generation of polymer powder of the styrene resin can be minimized. The powder should be as small as possible, since it shortens the life of the molding die. In addition, in consideration of the decomposition temperature of the polymerization initiator, the polymerization may be carried out while the styrene monomer is being impregnated, rather than starting the polymerization after impregnating the seed particles with the styrene monomer. When the polymerization is divided into a plurality of times, it is preferable to carry out the polymerization while feeding the styrene monomer at a rate of 0.001 to 0.1 parts by mass / sec per 100 parts by mass of seed particles in the second and subsequent polymerization steps.
[0050] The composite resin particles containing a flame retardant and a flame retardant auxiliary can be produced by a method of impregnating the flame retardant and the flame retardant auxiliary together with a styrene-based monomer into seed particles, or by a method of impregnating the flame retardant and the flame retardant auxiliary into particles after polymerization.
[0051] (Expandable particles) The expandable particles contain the composite resin particles and a foaming agent. Examples of the blowing agent include organic gases such as propane, n-butane, isobutane, n-pentane, isopentane, cyclopentane, n-hexane, and isohexane, and inorganic gases such as carbon dioxide, nitrogen, helium, argon, and air. These blowing agents can be used alone or in combination of two or more. The organic gas is preferably n-butane, isobutane, n-pentane, or isopentane, or a combination of these. The content of the foaming agent in the expandable particles is preferably 5 to 25 parts by mass based on 100 parts by mass of the composite resin particles.
[0052] The expanded beads obtained by pre-expanding the expandable particles have a reduced foaming moldability due to gas escape, so that the time from the production of the expanded beads to the filling of the expanded beads into a molding die cannot be secured long. However, when n-pentane, isopentane, cyclopentane, n-hexane, isohexane, etc. are used as the foaming agent, the gas escape from the expanded beads is suppressed, so that the time from the production of the expanded beads to the filling of the expanded beads into a molding die can be extended. Therefore, when the expanded beads of the present invention contain n-pentane, isopentane, cyclopentane, n-hexane, isohexane, etc. as the foaming agent, the time until filling can be extended, and the desired flame retardancy can be secured even if the flame retardancy of the foamed molded product is reduced due to the residual foaming agent. In other words, by adopting the composite resin particles of the present invention, the freedom of selection of the type and amount of the foaming agent is increased.
[0053] The expandable particles can be obtained, for example, by impregnating the composite resin particles with a foaming agent during or after the completion of polymerization. The impregnation can be carried out by a method known per se. For example, the impregnation during polymerization can be carried out by carrying out the polymerization reaction in a closed vessel and injecting the foaming agent into the vessel under pressure. The impregnation after the completion of polymerization can be carried out, for example, by injecting the foaming agent into the closed vessel into which the composite resin particles have been placed under pressure.
[0054] (Composite resin foam particles) Expanded beads (also generally referred to as pre-expanded beads) are particles obtained by pre-expanding composite resin particles. For example, expanded beads can be obtained by expanding expandable beads impregnated with a blowing agent. Expanded beads produced from the above composite resin particles are fused to each other by a medium with a low vapor pressure (e.g., water vapor), so that the energy required for expansion molding can be reduced and the equipment required for expansion molding can be simplified, thereby reducing the cost required for expansion molding.
[0055] The bulk density of the foam particles is 15 kg / m 3 ~200kg / m 3 is preferable, and 20 kg / m 3 ~100kg / m 3More preferably, 20 kg / m 3 ~50kg / m 3 If the bulk density is within this range, it is advantageous in that the foam molded article has high strength and is lightweight.
[0056] The expanded beads preferably have a spherical or nearly spherical shape, and the average particle size is preferably 1.0 mm to 9.0 mm, and more preferably 2.0 mm to 6.4 mm.
[0057] The expanded particles can be obtained by expanding the expandable particles to a desired bulk density by a known method. The expansion can be obtained by expanding the expandable particles using heated steam at a gauge pressure of preferably 0.05 MPa to 0.20 MPa, more preferably 0.06 MPa to 0.15 MPa.
[0058] (Foam molded body) The foamed molded article is a foamed article composed of a fusion body of the foamed beads, and is obtained, for example, by foaming the foamed beads. The foamed molded article uses the composite resin particles as a raw material, and therefore has excellent bending strength, impact resistance, and heat resistance.
[0059] The density of the foamed product is 15 kg / m 3 ~200kg / m 3 is preferable, and 20 kg / m 3 ~100kg / m 3 More preferably, 20 kg / m 3 ~50kg / m 3 When the density is within the above range, the foamed molded article is excellent in both lightness and strength. The density of the foamed molded article can be determined by the method described in the Examples.
[0060] The flexural strength of the foamed molded article can be, for example, 0.35 MPa or more, 0.35 MPa to 0.60 MPa, 0.38 MPa to 0.60 MPa, 0.40 MPa to 0.50 MPa, etc., and is preferably 0.40 MPa to 0.45 MPa. The flexural strength can be determined by the method described in the Examples.
[0061] The bending breaking point of the foamed molded article can be, for example, 15 mm or more, 15 mm to 50 mm, 15 mm to 40 mm, etc., preferably 20 mm to 40 mm, and more preferably 20 mm to 30 mm. The bending breaking point can be determined by the method described in the Examples.
[0062] The thermal dimensional change rate of the foamed molded article can be, for example, 1.5% or less, 1.2% or less, 1.1% or less, 0.5 to 1.5%, 0.5 to 1.2%, etc., and is preferably 0.5 to 1.1%. The thermal dimensional change rate can be determined by the method described in the Examples.
[0063] The falling ball impact value of the foamed molded article can be, for example, 25 cm or more, 31 cm or more, 25 cm to 60 cm, 31 cm to 50 cm, etc., preferably 32.5 cm to 50 cm, and more preferably 35 cm to 50 cm. The falling ball impact value can be determined by the method described in the Examples.
[0064] The flame retardancy of the foamed molded product is preferably such that the burning rate, as determined by the U.S. automobile safety standard FMVSS 302, particularly the method described in the examples, is 80 mm / min or less, more preferably 40 mm / min or less, and even more preferably 0 mm / min (self-extinguishing).
[0065] The foamed molded article can be obtained by filling the foamed beads into a mold of a foaming molding machine, and then heating the foamed beads to expand them while thermally fusing the beads together. Steam is preferably used as a heating medium.
[0066] The composite resin foamed beads of the present invention can be sufficiently foamed and fused even with a medium (e.g., water vapor) of low pressure (e.g., gauge pressure of 0.05 MPa to 0.16 MPa, 0.05 MPa to 0.15 MPa, 0.05 MPa to 0.12 MPa, or 0.05 MPa to 0.11 MPa, 0.05 MPa to 0.10 MPa), so the energy required for foam molding can be reduced and the equipment required for foam molding can be simplified, resulting in reduced costs for foam molding (i.e., excellent productivity). Other production conditions such as process temperature, process pressure and process time in each production step are appropriately set depending on the production equipment, raw materials and the like used.
[0067] The foamed molded article can be used, for example, as automobile parts, cushioning materials, packaging materials, building materials, shoe parts, sporting goods, etc. Specifically, it can be used as tire core materials for bicycles, wheelchairs, etc.; interior materials, seat core materials, shock absorbing parts (e.g., bumper core materials), vibration absorbing parts, etc. for transport equipment such as automobiles, railroad cars, and airplanes; midsole materials, insole materials, or outsole materials for shoes; core materials for hitting tools for sporting goods such as rackets and bats; protective gear for sporting goods such as pads and protectors; medical, nursing, welfare, or health care products such as pads and protectors; fenders; floats; toys; floor underlay materials; wall materials; beds; cushions; electronic parts, various industrial materials, and transport containers for foods, etc. The material is preferably used as an interior material for an automobile, a shock absorbing material, a vibration absorbing material, or a packaging material for parts. EXAMPLES
[0068] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these. The methods for determining various physical properties in the examples are described below.
[0069] (MFR of polypropylene resin and ethylene-vinyl acetate polymer) The MFR was measured at 190° C. under a load of 2.16 kg in accordance with JIS K6922-1:1998.
[0070] (Melting points of polypropylene resin and ethylene-vinyl acetate copolymer) The melting point was measured by the method described in JIS K7122:1987 "Method for measuring heat of transition of plastics". That is, a differential scanning calorimeter RDC220 type (manufactured by Seiko Denshi Kogyo Co., Ltd.) was used, 7 mg of the sample was filled in the measurement container, and the temperature was increased, decreased, and increased again at a rate of 10°C / L between room temperature and 220°C under a nitrogen gas flow rate of 30 mL / min, and the melting peak temperature of the DSC curve during the second heating was taken as the melting point. In addition, when there were two or more melting peaks, the lower peak temperature was taken as the melting point.
[0071] (Number average molecular weight (Mn) and mass average molecular weight (Mw) of ethylene-vinyl acetate copolymer) Specifically, the molecular weight was measured as follows. 6 mL of O-dichlorobenzene was added to a container containing 6 mg of sample, and the container was sealed to prepare a solution. The solution was prepared by dissolving the sample by heating at 160°C for 1 hour using a DF-8200 manufactured by Tosoh Corporation. This solution was used as the measurement sample and measured by gel permeation chromatography under the following measurement conditions. Standard polystyrene was measured in advance, and the average molecular weight (Mn, Mw) of the sample was obtained from a calibration curve of the standard polystyrene that had been prepared in advance. Equipment used: Tosoh Corporation "HLC-8321GPC / HT" gel permeation chromatograph Guard column: TSKgel guardcolumn HHR(30)HT2 (7.5mmI.D.×7.5cm×1) manufactured by Tosoh Corporation Column: Tosoh Corporation TSKgel GMHHR-H(20)HT2 (7.8mmI.D.×30cm)×3 Mobile phase: O-dichlorobenzene Sample flow rate: 1.0mL / min Reference flow rate: 0.5mL / min Detector: RI Sample concentration: 0.1wt% Injection volume: 300μL Measurement time: 34 min (Temperature settings for each part of the device) Solvent stocker: 40℃ Column oven (column temperature): 160℃ Sample table: 160℃ Injection valve: 160℃ Detector: 160℃ The standard polystyrene samples used for the calibration curve were "High polymer kit" and "oligomer kit" manufactured by Tosoh Corporation, with mass average molecular weights of 8,420,000, 5,480,000, 2,110,000, 1,090,000, 706,000, 427,000, 190,000, 96,400, 37,900, 17,400, 5,060, 2,550, 1,013, and 589. The above-mentioned standard polystyrene for the calibration curve was grouped into A (8,420,000, 1,090,000, 190,000, 17,400, 1,013), B (5,480,000, 706,000, 96,400, 5,060, 589) and C (2,110,000, 427,000, 37,900, 2,550), and then 10 mg of A was weighed out and dissolved in 30 mL of O-dichlorobenzene. 10 mg of B and C were also weighed out and dissolved in 30 mL of O-dichlorobenzene. The standard polystyrene calibration curve was obtained by injecting 300 μL of each of A, B and C solutions and creating a calibration curve (cubic equation) from the retention times obtained after measurement. The average molecular weight was calculated using the calibration curve.
[0072] (Bulk density of composite resin foam particles) Put the composite resin foam particles into a measuring cylinder with a length of 500 cm 3 However, the graduated cylinder was visually inspected from the horizontal direction to see if even one composite resin foam particle was found to be within 500 cm 3 If the weight reaches the mark, the filling is complete. Next, the mass of the composite resin foam particles filled in the measuring cylinder is weighed to two decimal places, and this mass is designated as W (g). The bulk density of the composite resin foam particles is calculated using the following formula. Bulk density (kg / m 3 )=(W / 500)×1000
[0073] (Amount of powder generated during the production of composite resin foam beads) Bulk density 0.025g / cm 35 kg of pre-expanded composite resin foam particles were classified using a sieve with a nominal mesh size of 0.9 mm. The mass (D(g)) of the powder that passed through the 0.9 mm mesh size was measured, and the amount of powder (P) per 5 kg of composite resin foam particles was calculated using the following formula. P(%)=D / (5×1000)×100 Since powder can shorten the life of the mold, the smaller the powder content, the better. The powder content should be 0.04% or less, more preferably 0.03% or less, and even more preferably 0.02% or less.
[0074] (Density of foamed molded body) The mass (a) and volume (b) of a test piece (75 mm x 300 mm x 35 mm) cut out from the foam molded product (dried at 50°C for at least 4 hours after molding) are measured to have three or more significant figures, and the density of the foam molded product (g / cm3) is calculated using the formula (a) / (b). 3 ) was sought.
[0075] (Flexural strength and bending breaking point of foamed molded products) The bending strength (average maximum bending strength) and bending breaking point were measured according to the method described in JIS K7221-1:2006 "Rigid foam plastics - Bending test - Part 1: Determination of deflection characteristics." That is, using a Tensilon universal testing machine UCT-10T (manufactured by Orientec Co., Ltd.) and universal testing machine data processing software UTPS-237 (manufactured by Softbrain Co., Ltd.), the rectangular parallelepiped test specimen size was 25 mm wide x 130 mm long x 20 mm thick (skin surface only on the pressure surface side), the test speed was 10 mm / min, the pressure wedge was 5R, the support stand was 5R, and the distance between supports was 100 mm, and pressure was applied so that the surface of the test specimen without the skin was stretched. The number of test pieces was five, and they were conditioned for 16 hours in a class 2 standard atmosphere of "23 / 50" (temperature 23°C, relative humidity 50%) according to JIS K7100:1999 "Plastics - Standard atmosphere for conditioning and testing", and then the above-mentioned measurements were carried out in the same standard atmosphere. The bending strength (MPa) was calculated using the following formula. R = (1.5F R ×L / bd 2 ) x 103 R: Bending strength (MPa) F R : Maximum load (kN) L: Distance between fulcrums (mm) b: width of test piece (mm) d: thickness of test piece (mm) A bending strength of 0.35 MPa or more is desirable, and a bending strength of 0.40 MPa or more can be evaluated as excellent. In this test, the fracture detection sensitivity was set to 0.5%, and when the decrease in the load compared to the immediately preceding sampling point exceeded the set value of 0.5% (deflection: 30 mm), the immediately preceding sampling point was measured as the bending fracture displacement (mm), and the average of the five tests was calculated to be the bending fracture point (mm). A bending fracture point of 15 mm or more is desirable, and a bending fracture point of 20 mm or more can be evaluated as having excellent flexibility.
[0076] (Dimensional change rate of foam molded body due to heating) The thermal dimensional change rate of the foamed molded body was measured by the method B described in JIS K 6767:1999 "Foamed plastics - Polyethylene - Test method". A test piece measuring 150 mm long x 150 mm wide x 20 mm high was cut out from the foamed molded body. On the surface of the test piece, three straight lines oriented in the vertical direction and 50 mm long were drawn parallel to each other at 50 mm intervals, and three straight lines oriented in the horizontal direction and 50 mm long were drawn parallel to each other at 50 mm intervals. The test piece was then left in a hot air circulation dryer at 80°C for 168 hours, and then taken out and left in a place under standard conditions (20±2°C, humidity 65±5%) for 1 hour. Next, the lengths of the six straight lines drawn on the surface of the test piece were measured, and the arithmetic mean value L1 of the lengths of the six straight lines was calculated. The degree of change S was calculated based on the following formula, and the absolute value of the degree of change S was taken as the thermal dimensional change rate (%). S = 100 × (L1 - 50) / 50 If the rate of dimensional change upon heating is 1.5% or less, it can be evaluated as having a low rate of dimensional change and good dimensional stability, and if it is 1.1% or less, it can be evaluated as having even better dimensional stability.
[0077] (Burning rate and flame retardancy of foamed molded products) The burning rate (mm / min) was measured by a method conforming to the US automobile safety standard FMVSS 302. The test specimen (bulk expansion ratio 40 times) was 350 mm × 100 mm × 12 mm (thickness), and at least two sides of the 350 mm × 100 mm had a skin. The flame retardancy was evaluated based on the burning rate according to the following criteria. If the fire is extinguished before reaching the measurement start point, the burning rate is set to 0 mm / min and the product can be evaluated as self-extinguishing. If the burning rate is 80 mm / min or less, the product can be evaluated as having excellent flame retardancy. Self-extinguishing is more preferable for the flammability of foamed molded products.
[0078] (Falling ball impact value) A sample was prepared by cutting the foamed molded body to a size of 215 mm x 40 mm x 20 mm. This sample was placed on a pair of holding members arranged with a span of 155 mm, and then a steel ball weighing 321 g was dropped from a specified height onto the midpoint between the two holding members and the center position in the width direction of the sample, and the presence or absence of damage to the sample was confirmed. This test was repeated by changing the height from which the steel ball was dropped, and the minimum height at which the sample was broken was taken as the falling ball impact value, and the impact strength was evaluated. Therefore, the higher the falling ball impact value, the higher the impact strength. If the ball impact value is 25cm or more, it can be evaluated as having practical shock absorption, and if it is 30cm or more, it can be evaluated as having excellent shock absorption.
[0079] (Fusion rate of foamed molded body) The upper surface of the foam molded article had a rectangular parallelepiped shape with an upper surface of 400 mm in length x 300 mm in width and a thickness of 30 mm. A cut line of 300 mm in length and about 5 mm in depth was made in the horizontal direction with a cutter, and the foam molded article was divided into two along the cut line, and the fracture surface was observed. An arbitrary range containing 50 or more expanded beads was set, and within this range, the number (a) of expanded beads that had broken internally rather than on the surface (strongly heat-fused expanded beads) and the number (b) of expanded beads that had broken at the interface between the expanded beads (weakly heat-fused expanded beads) were counted, and the fusion rate (%) was calculated using the following formula. Fusion rate (%) = (a / (a+b)) x 100
[0080] (Moldability of foamed molded products; water vapor pressure) The composite resin foam particles were filled into a 300mm x 400mm x 30mm mold of an expansion molding machine, and heated with steam to expand the composite resin foam particles while thermally fusing the composite resin foam particles together. When heating with water vapor (for 50 seconds), the steam pressure of the water vapor was changed in increments of 0.01 MPa from 0.08 MPa to 0.25 MPa, and the fusion rate of the resulting foamed molded product was determined for each value. Moldability was evaluated based on the lowest steam pressure value (minimum steam pressure value) at which the fusion rate was 90% or more. If a foamed molded product with good fusion can be obtained at a low steam pressure, the molding equipment can be simplified and the manufacturing energy can be reduced, resulting in lower manufacturing costs and improved productivity. If a foamed molded product with a fusion rate of 90% or more can be obtained at a steam pressure of 0.16 MPa or less, preferably 0.10 MPa or less, a foamed molded product with good fusion can be obtained with low steam pressure adjustment, resulting in good moldability and high productivity.
[0081] (Storage stability (discoloration of foam molded products)) Accelerated exposure tests were carried out on test pieces measuring 300 mm long x 400 mm wide in a dark room using a thermohygrometer under the following conditions. The test pieces were white. Test chamber temperature: 55-65℃, relative humidity: 50-60%, test time: 168hr, number of test pieces: 10 The test pieces after the accelerated exposure test were checked for changes in the appearance color before and after the test. When no partial discoloration from the white color was observed in any of the 10 test pieces, it was judged that there was no discoloration of the foam molded product. When even a part of the test piece was confirmed to have changed from the white color, it was judged that there was discoloration of the foam molded product.
[0082] (Polypropylene resin, etc.) The polypropylene-based resin (PP) used in the examples and the high-density polyethylene resin (HDPE) used for comparison are as follows. The physical properties of the polypropylene-based resin and the high-density polyethylene resin are shown in Table 1. F744NP: Random copolymer of PP (Prime Polymer, ethylene content 7% by mass) S-131: PP random copolymer (Sumitomo Chemical Co., Ltd., ethylene content 5% by mass) PL500A: PP homopolymer (manufactured by SunAllomer) 10S65B: High density polyethylene (manufactured by Tosoh Corporation)
[0083] [Table 1]
[0084] (Ethylene-vinyl acetate copolymer, etc.) The ethylene-vinyl acetate copolymer (EVA) used in the examples and the ethylene-ethyl acrylate copolymer (EEA) used for comparison are as follows. The physical properties of the ethylene-vinyl acetate copolymer and the ethylene-ethyl acrylate copolymer are shown in Table 2. EF0505: Ethylene-vinyl acetate copolymer (Asahi Kasei Corporation, vinyl acetate content 4.7% by mass) EF0510: Ethylene-vinyl acetate copolymer (Asahi Kasei Corporation, vinyl acetate content 5% by mass) LV430: Ethylene-vinyl acetate copolymer (Japan Polyethylene Corporation, vinyl acetate content 15% by mass) 514R: Ethylene-vinyl acetate copolymer (Tosoh Corporation, product number 514R, vinyl acetate content 5% by mass) A1100: Ethylene-ethyl acrylate copolymer (Japan Polyethylene Corporation, product number A1100, ethyl acrylate content 10% by mass)
[0085] [Table 2]
[0086] Other materials used in the examples are listed below. Fine silica: Silica (manufactured by Nippon Aerosil Co., Ltd., product number AEROSIL200) Talc: Talc master batch manufactured by Nitto Funka Co., Ltd. (product name "Talpet 70P", average particle size (D50) 12 μm, specific surface area 8.5 m 2 / g, talc purity 70% (mass%) TAIC-6B: Tris(2,3-dibromopropyl)isocyanurate (manufactured by Nippon Kasei Co., Ltd.) Biscumyl: 2,3-dimethyl-2,3-diphenylbutane (manufactured by Nouryon Chemical Industries, product number Perkadox 30)
[0087] Example 1 [Preparation of seed particles] F744NP as the polypropylene resin (A) and EF0505 as the ethylene-vinyl acetate copolymer (B) were charged in a mass ratio of 40:60 into a tumbler mixer and mixed for 10 minutes. Finely powdered silica as an inorganic component was added thereto in an amount of 0.25 mass% relative to the total mass of the polypropylene resin (A) and the ethylene-vinyl acetate copolymer (B), and further mixed for 10 minutes to obtain a resin mixture (base resin). The obtained resin mixture was fed to an extruder and melt-kneaded at a temperature of 230 to 250°C, granulated by an underwater cutting method, and cut into elliptical spherical (egg-shaped) particles to obtain polypropylene-based resin particles (seed particles, average mass 0.6 mg) modified with ethylene-vinyl acetate copolymer.
[0088] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 600 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.6 g of dicumyl peroxide (polymerization initiator) was dissolved in 300 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0089] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 120°C over 10 minutes. Next, a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 1100 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 120°C for 1 hour to impregnate the modified polypropylene resin particles with the styrene monomer. Then, a dispersion medium prepared by dispersing 3 g of ethylenebisstearic acid amide (cell bubble regulator) in 100 g of pure water was dropped over 30 minutes, and after dropping, the mixture was held at 115°C for 1 hour to impregnate the seed particles with the styrene monomer and the cell bubble regulator. After impregnation, the temperature was raised to 140°C and the mixture was held at this temperature for 3 hours to polymerize (second polymerization).
[0090] Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 10 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (the ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene was 30:70). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0091] [Preparation of expandable particles] 2 kg (100 parts by mass) of composite resin particles, 2 kg of water, and 2.0 g of sodium dodecylbenzenesulfonate (surfactant) were added to a 5-liter autoclave equipped with a stirrer. In addition, 300 g (520 mL, 15 parts by mass per 100 parts by mass of composite resin particles) of isopentane was added as a blowing agent, and the temperature was raised to 70°C. Stirring was continued for 4 hours to obtain expandable particles. The mixture was then cooled to 30°C or lower, and the autoclave was depressurized after cooling was completed. The surfactant was immediately washed with distilled water, and the expandable particles were obtained by dehydrating and drying.
[0092] [Preparation of foam particles] The obtained expandable resin particles are charged into a cylindrical pre-expander equipped with an agitator and has an internal volume of 50 L, and heated with steam at 0.02 MPa while stirring to a bulk density of 25 kg / m 3 The expanded particles (sometimes generally referred to as pre-expanded particles) were produced. The expanded particles were classified using a 0.9 mm mesh sieve, and the powder amount was measured by weighing the mass of the powder discharged as the classified off-particle.
[0093] [Preparation of foam molded products] The resulting expanded beads were left to stand at 23°C for 1 day, and then loaded into a molding die (length 400 mm × width 300 mm × thickness 30 mm) of an automatic expanded bead molding machine (DABO Japan, DPM-7454). Steam at 0.09 MPa was introduced into the die for 50 seconds to heat and expand the expanded beads, and the expanded molded product was cooled until the maximum surface pressure of the expanded molded product decreased to 0.01 MPa, resulting in a density of 25 kg / m 3 A foamed molded article of 100 g was obtained. The foamed molded article obtained had a good appearance and fusion. The foamed molded article obtained was subjected to various tests. The results are shown in Table 3.
[0094] Examples 2 to 6 and Comparative Examples 3 and 4 The foamed molded articles of Examples 2 to 5 and Comparative Examples 3 and 4 were produced in the same manner as in Example 1, except that the materials, amounts, expanded particle bulk densities, etc. shown in Table 3 were used. The resulting foamed molded articles were subjected to various tests. The results are shown in Table 3. The meanings of the terms in Table 3 are as follows: Mw / Mn of B: Ratio of mass average molecular weight to number average molecular weight of ethylene-vinyl acetate copolymer (B) A:B mass ratio: the mass ratio of polypropylene resin (A) to ethylene-vinyl acetate copolymer (B) Inorganic component content (%): The proportion of inorganic components added to the total mass of the polypropylene resin (A) and the ethylene-vinyl acetate copolymer (B) (mass%) A+B:PS mass ratio: The ratio of the total mass of the polypropylene resin (A) and the ethylene-vinyl acetate copolymer (B) to the mass of polystyrene Amount of flame retardant added: The proportion of flame retardant added to the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) (mass%) Amount of flame retardant additive: The proportion of flame retardant additive added to the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) (% by mass) Gas type A: butane as a foaming agent (normal butane:isobutane = 7:3 (volume ratio)) Gas type B: isopentane as blowing agent
[0095] Example 7 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 1, except that the materials and amounts shown in Table 3 were used.
[0096] [Preparation of composite resin particles] A dispersion medium was obtained by adding 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water to a 5-liter autoclave equipped with a stirrer. 1000 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 1.0 g of dicumyl peroxide (polymerization initiator) was dissolved in 500 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0097] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 120°C over 10 minutes. Next, a liquid in which 3 g of dicumyl peroxide (polymerization initiator) was dissolved in 500 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 120°C for 1 hour to impregnate the modified polypropylene resin particles with the styrene monomer. Then, a dispersion medium prepared by dispersing 3 g of ethylenebisstearic acid amide (cell bubble regulator) in 100 g of pure water was dropped over 30 minutes, and after dropping, the mixture was held at 120°C for 1 hour to impregnate the seed particles with the styrene monomer and the cell bubble regulator. After the impregnation, the temperature was raised to 140°C and maintained at this temperature for 3 hours to polymerize (second polymerization) to produce composite resin particles (ratio of total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to polystyrene mass: 50:50). Next, the mixture was cooled to 30°C or lower, and the composite resin particles were removed from the autoclave.
[0098] [Preparation of expandable particles, expanded particles, and expanded molded products] In the preparation of the expandable particles, the gas type is A, and the bulk density of the expanded particles is 33 kg / m 3 The density of the foamed molded body is 33 kg / m 3 Expandable beads, expanded beads, and expanded molded articles were obtained in the same manner as in Example 1, except that the above-mentioned procedure was followed.
[0099] Example 8 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 1, except that the materials and amounts shown in Table 4 were used.
[0100] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 600 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.6 g of dicumyl peroxide (polymerization initiator) was dissolved in 300 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0101] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 125°C over 10 minutes. Next, a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 20 g of butyl acrylate and 1080 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 125°C for 1 hour to impregnate the modified polypropylene resin particles with butyl acrylate and styrene monomer. Then, a dispersion medium prepared by dispersing 3 g of ethylenebisstearic acid amide (cell bubble regulator) in 100 g of pure water was dropped over 30 minutes, and after dropping, the mixture was held at 125°C for 1 hour to impregnate the seed particles with butyl acrylate, styrene monomer, and cell bubble regulator. After impregnation, the mixture was heated to 140°C and held at this temperature for 3 hours to polymerize (second polymerization).
[0102] Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 20 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (the ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene was 30:70). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0103] [Preparation of expandable particles, expanded particles, and expanded molded products] In the preparation of the expandable particles, the same procedure as in Example 1 was carried out except that the gas type was changed to A, to obtain expandable particles, expanded particles, and foamed molded articles.
[0104] Example 9 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 1, except that the materials and amounts shown in Table 4 were used.
[0105] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 600 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.6 g of dicumyl peroxide (polymerization initiator) was dissolved in 300 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0106] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 125°C over 10 minutes. Next, a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 30 g of butyl acrylate and 1070 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 125°C for 1 hour to impregnate the modified polypropylene resin particles with butyl acrylate and styrene monomer. Then, a dispersion medium prepared by dispersing 3 g of ethylenebisstearic acid amide (cell bubble regulator) in 100 g of pure water was dropped over 30 minutes, and after dropping, the mixture was held at 125°C for 1 hour to impregnate the seed particles with butyl acrylate, styrene monomer, and cell bubble regulator. After impregnation, the mixture was heated to 140°C and held at this temperature for 3 hours to polymerize (second polymerization).
[0107] Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 20 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (the ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene was 30:70). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0108] [Preparation of expandable particles, expanded particles, and expanded molded products] In the preparation of the expandable particles, the same procedure as in Example 1 was carried out except that the gas type was changed to A, to obtain expandable particles, expanded particles, and foamed molded articles.
[0109] Example 10 [Preparation of seed particles] F744NP as polypropylene resin (A) and EF0505 as ethylene-vinyl acetate copolymer (B) were charged in a mass ratio of 80:20 into a tumbler mixer and mixed for 10 minutes. Carbon black master batch (manufactured by Dainichiseika Chemicals Mfg. Co., Ltd., product name: PPRM-10H381, carbon black content 45 mass%) was added thereto in an amount such that the carbon black content was 5 mass% relative to the total mass of the polypropylene resin (A) and the ethylene-vinyl acetate copolymer (B), and further mixed for 10 minutes to obtain a resin mixture (base resin). The obtained resin mixture was fed to an extruder and melt-kneaded at a temperature of 230 to 250°C, granulated by an underwater cutting method, and cut into elliptical spherical (egg-shaped) particles to obtain polypropylene-based resin particles (seed particles, average mass 0.6 mg) modified with ethylene-vinyl acetate copolymer.
[0110] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 600 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.6 g of dicumyl peroxide (polymerization initiator) was dissolved in 300 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0111] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 125°C over 10 minutes. Next, a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 20 g of butyl acrylate and 1080 g of styrene monomer was dropped at a rate equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 125°C for 1 hour to impregnate the modified polypropylene resin particles with butyl acrylate and styrene monomer. After impregnation, the mixture was heated to 140°C and held at this temperature for 3 hours to polymerize (second polymerization).
[0112] Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 20 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (the ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene was 30:70). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0113] [Preparation of expandable particles, expanded particles, and expanded molded products] In the preparation of the expandable particles, the same procedure as in Example 1 was carried out except that the gas type was changed to A, to obtain expandable particles, expanded particles, and foamed molded articles.
[0114] Example 11 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 10, except that the materials and amounts shown in Table 4 were used.
[0115] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 800 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 1.0 g of dicumyl peroxide (polymerization initiator) was dissolved in 400 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0116] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 125°C over 10 minutes. Next, a liquid in which 4 g of dicumyl peroxide (polymerization initiator) was dissolved in 10 g of butyl acrylate and 790 g of styrene monomer was dropped at a rate equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the modified polypropylene resin particles were impregnated with butyl acrylate and styrene monomer by holding at 125°C for 1 hour. Then, the temperature was raised to 140°C and the mixture was held at this temperature for 3 hours to polymerize (second polymerization). Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 20 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene: 40:60). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0117] [Preparation of expandable particles, expanded particles, and expanded molded products] In the preparation of the expandable particles, the same procedure as in Example 1 was carried out except that the gas type was changed to A, to obtain expandable particles, expanded particles, and foamed molded articles.
[0118] Example 12 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 10, except that the materials and amounts shown in Table 4 were used.
[0119] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 800 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.8 g of dicumyl peroxide (polymerization initiator) was dissolved in 400 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0120] Next, a dispersion of 3 g of sodium dodecylbenzenesulfonate dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 125°C over 10 minutes. Next, a solution of 4 g of dicumyl peroxide (polymerization initiator) dissolved in 800 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 125°C for 1 hour to impregnate the modified polypropylene resin particles with the styrene monomer. The mixture was then heated to 140°C and held at this temperature for 3 hours to polymerize (second polymerization). Into this reaction liquid, 60 g of TAIC-6B as a flame retardant and 20 g of bismuth as a flame retardant auxiliary were added. After addition, the temperature of the reaction system was raised to 140°C, and stirring was continued for 3 hours to produce flame retardant-containing composite resin particles (ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene: 40:60). Next, it was cooled to 30°C or less, and the composite resin particles were taken out of the autoclave.
[0121] [Preparation of expandable particles, expanded particles, and expanded molded products] In the same manner as in Example 1, expandable beads, expanded beads and an expanded molded article were obtained.
[0122] Comparative Example 1 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 1, except that the materials and amounts shown in Table 3 were used.
[0123] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 1400 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 600 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with styrene monomer. After impregnation, the temperature was raised to 140° C. and polymerization was carried out at this temperature for 4 hours to produce composite resin particles (a ratio of the total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to the mass of polystyrene of 70:30). Next, the mixture was cooled to 30° C. or less, and the composite resin particles were taken out of the autoclave.
[0124] [Preparation of expandable particles, expanded particles, and expanded molded products] Expandable beads, expanded beads and an expanded molded article were produced in the same manner as in Example 1, except that the gas type was changed to A.
[0125] Comparative Example 2 [Preparation of seed particles] Seed particles were produced in the same manner as in Example 1, except that the materials and amounts shown in Table 3 were used.
[0126] [Preparation of composite resin particles] A dispersion medium was obtained by putting 40 g of magnesium pyrophosphate (dispersant), 0.6 g of sodium dodecylbenzenesulfonate (surfactant), and 2 kg of pure water into a 5-liter autoclave equipped with a stirrer. 800 g of seed particles were dispersed in the dispersion medium at 30° C. and held for 10 minutes, and then heated to 60° C. to obtain a suspension. Furthermore, while holding this suspension at 60° C., a solution in which 0.8 g of dicumyl peroxide (polymerization initiator) was dissolved in 400 g of styrene monomer was dropped over 30 minutes, and then held for 30 minutes to impregnate the seed particles with the styrene monomer. After impregnation, the temperature was raised to 140° C., and polymerization (first polymerization) was carried out at this temperature for 2 hours.
[0127] Next, a dispersion liquid in which 3 g of sodium dodecylbenzenesulfonate was dispersed in 20 g of pure water was dropped into the reaction liquid cooled to 120°C over 10 minutes. Next, a liquid in which 5 g of dicumyl peroxide (polymerization initiator) was dissolved in 800 g of styrene monomer was dropped at a speed equivalent to 0.05 parts by mass / second per 100 parts by mass of seed particles. After dropping, the mixture was held at 120°C for 1 hour to impregnate the modified polypropylene resin particles with the styrene monomer. Then, a dispersion medium prepared by dispersing 3 g of ethylenebisstearic acid amide (cell bubble regulator) in 100 g of pure water was dropped over 30 minutes, and after dropping, the mixture was held at 120°C for 1 hour to impregnate the seed particles with the styrene monomer and the cell bubble regulator. After the impregnation, the temperature was raised to 140°C and maintained at this temperature for 3 hours to polymerize (second polymerization) to produce composite resin particles (ratio of total mass of polypropylene resin (A) and ethylene-vinyl acetate copolymer (B) to polystyrene mass: 40:60). Next, the mixture was cooled to 30°C or lower, and the composite resin particles were removed from the autoclave.
[0128] [Preparation of expandable particles, expanded particles, and expanded molded products] Expandable beads, expanded beads and an expanded molded article were produced in the same manner as in Example 1, except that the gas type was changed to A.
[0129] [Table 3]
[0130] [Table 4]
[0131] In Comparative Example 1 in which the A+B:PS ratio was 70:30, the powder amount was as high as 0.05 mass %, the minimum steam pressure value was as high as 0.28 MPa, and the falling ball impact value was small.
[0132] In Comparative Example 2, in which ethylene-vinyl acetate copolymer (EVA) was not used and only a polypropylene-based resin was used as the base resin, the minimum steam pressure was as high as 0.18 MPa, and a large amount of energy was required for foam molding.
[0133] In Comparative Example 3, in which high-density polyethylene resin was used instead of polypropylene resin, self-extinguishing was not observed and the flame retardancy was inferior to the other examples. In addition, in the accelerated storage stability test, the foam molded body was colored light red.
[0134] In Comparative Example 4, in which an ethylene-ethyl acrylate copolymer (EEA) was used, the powder amount was as high as 0.07% by mass.
[0135] Examples 1 to 7 showed excellent results in all evaluation items, and in particular, Examples 1 and 2 showed better results in all evaluation items. Furthermore, the foamed molded product of the present invention showed excellent flame retardancy even without blending a flame retardant (Example 6).
[0136] In Examples 8 to 11, although the amount of polypropylene resin relative to the ethylene-vinyl acetate copolymer was large, the polystyrene resin contained a resin component derived from butyl acrylate, so that the minimum vapor pressure value could be kept low, and the energy required for foam molding could be reduced.
[0137] Although Examples 10 to 12 contained a carbon component, they exhibited sufficient mechanical properties (flexural strength, bending breaking point, and falling ball impact value).
Claims
1. Composite resin particles containing a polypropylene-based resin, an ethylene-vinyl acetate copolymer, and a polystyrene-based resin, The composite resin particles have a polypropylene resin content of 2 to 35% by mass, an ethylene-vinyl acetate copolymer content of 3 to 50% by mass, and a polystyrene resin content of 40 to 95% by mass, based on the total mass of the composite resin particles.
2. 2. The composite resin particle according to claim 1, wherein the content of said ethylene-vinyl acetate copolymer in said composite resin particle is 60 to 1000 parts by mass per 100 parts by mass of said polypropylene-based resin.
3. the content of the ethylene-vinyl acetate copolymer in the composite resin particles is 10 to 60 parts by mass relative to 100 parts by mass of the polypropylene-based resin; The composite resin particles according to claim 1, wherein the polystyrene-based resin contains a resin component derived from a (meth)acrylic acid ester and a resin component derived from a styrene-based monomer, and the resin component derived from the (meth)acrylic acid ester is contained in an amount of 0.05 to 5.00 mass% of the mass of the resin component derived from the styrene-based monomer.
4. The composite resin particles according to any one of claims 1 to 3, wherein the total mass content of the polypropylene-based resin and the ethylene-vinyl acetate copolymer in the composite resin particles / the mass content of the polystyrene-based resin in the composite resin particles is 5 / 95 to 60 / 40.
5. 5. The composite resin particle according to claim 1, wherein the ethylene-vinyl acetate copolymer has a melting point of 100 to 120°C.
6. The composite resin particle according to any one of claims 1 to 5, wherein the ethylene-vinyl acetate copolymer has a ratio (Mw / Mn) of its mass average molecular weight (Mw) to its number average molecular weight (Mn) of 1.0 to 7.
0.
7. 7. The composite resin particle according to claim 1, wherein the ethylene-vinyl acetate copolymer has a melt flow rate of 0.5 g / 10 min to 10 g / 10 min.
8. The composite resin particle according to any one of claims 1 to 7, wherein the polypropylene resin has a melting point of 130 to 150°C.
9. The composite resin particles according to any one of claims 1 to 8, wherein the polypropylene-based resin is a random polypropylene.
10. The composite resin particles according to any one of claims 1 to 9, further comprising a flame retardant, the content of which is 0.5 to 10 mass % of the mass of the composite resin particles excluding the flame retardant.
11. The composite resin particle according to claim 10 , wherein the flame retardant is a halogen-based flame retardant.
12. 12. The composite resin particle according to claim 1, further comprising an inorganic component, the content of which is 0.01 to 5% by mass of the composite resin particle.
13. The composite resin particle according to claim 12, wherein the inorganic component is talc or silica.
14. 14. The composite resin particle according to claim 1, which is a seed polymerization particle obtained by impregnating and polymerizing a styrene monomer into a seed particle containing the polypropylene resin and the ethylene-vinyl acetate copolymer.
15. 15. An expanded bead comprising the composite resin bead according to claim 1.
16. Bulk density: 10 kg / m 3 ~200kg / m 3 16. The expanded beads of claim 15,
17. A foamed molded article comprising the foamed beads according to claim 15 or 16.
18. Density: 20 kg / m 3 ~50kg / m 3 The foamed molded article according to claim 17,
19. An automobile component comprising the foamed molded article according to claim 17 or 18.
Citation Information
Patent Citations
Band
JP1987051409A
Polyethylene resin composition and molded product thereof
JP1996208916A
Composite resin particle, foamable resin particle, method for producing them, foamed particle and foamed molding
JP2012167148A
High density polyethylene resin particle, compound resin particle, foam particle, and foam molded body
JP2015189912A
Composite resin particle, manufacturing method therefor, foamable particle, foam particle, foam molded body and exterior material for automobile
JP2018053029A